PENGARUH RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, DAN CAPITAL TERHADAP PREDIKSI FINANCIAL DISTRESS PADA BANK PERKREDITAN RAKYAT - Wijayanti, Kristina Nimas; Sari, Inayah Adi; Indriasih, Dewi (PERMANA, 2018)
This study aims to determine the effect of Risk Based Bank Rating on the prediction of financial distress in Rural Banks in the area of ex Residency of Pekalongan with the period of research in 2013 until 2017. This study of financial distress uses a quantitative approach towards all BPR in Indonesia by using purposive sampling method. Data analysis method used is logistic regression analysis with the dependent variable in the form of dummy variables, namely 1 for non-financial distress and 2 for financial distress. Determination of the financial distress category was determined based on the Financial Services Authority Regulation No.5 / POJK.03 / 2015, that BPR with core capital below Rp6 billion indicated experiencing financial difficulties and vice versa. The results of the research showed that (1) Risk Profile represented by the LDR and NPL ratios had a positive and insignificant effect on financial distress. (2) Good Corporate Governance (GCG) represented by the composite value of the self-assessment report on the application of BPR governance has a positive effect but not significant to financial distress. (3) Earnings represented by the ROA ratio have a positive and insignificant effect on financial distress. (4) Capital represented by the CAR ratio has a negative effect and is not significant to financial distress.Keywords: Rural Bank, financial distress, Risk Based Bank Rating, profile risk, Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), Good Corporate Governance (GCG),Earnings, Return On Asset (ROA), Capital Adequacy Ratio (CAR), logistic regression